The Genesis of the Insurgency in Jammu and Kashmir, and in the North East, and future prospects - Krishna Rao, K. V., Gen. (New Delhi United Service Institution of India, 1997)
Lecture delivered by the speaker in 1997, at the USI.
Keywords: India--Jammu and Kashmir -- India -- India, Northeastern